Ultraviolet Photodetector Based on Mg 0.67 Ni 0.33 O Thin Film on SrTiO 3 - Sarcan, Fahrettin; Orchard, Sam; Kuerbanjiang, Balati; Skeparovski, Aleksandar; Lazarov, Vlado K.; Erol, Ayse (Wiley, 2020)
Herein, a new heterostructured ultraviolet metal–semiconductor–metal photodetector based on Mg0.67Ni0.33O thin film and SrTiO3 is reported. The metal–semiconductor–metal photodetector comprises a 22 nm epilayer of Mg0.67Ni0.33O grown on SrTiO3 (111) substrate by molecular beam epitaxy. A comparison of responsivities of the Mg0.67Ni0.33O–SrTiO3 photodetector and reference SrTiO3 photodetector shows that the heterostructured detector has close to an order of magnitude enhanced responsivity in the deep‐ultraviolet region. The responsivity of the Mg0.67Ni0.33–SrTiO3‐based photodetector at 320 nm is 415 mA W−1, with dark current lower than 40 pA at a bias of 10 V. The rise and fall times of Mg0.67Ni0.33O–SrTiO3 photodetector are 10.7 and 8.6 ms, respectively, with the rise time more than two orders of magnitude shorter than the reference SrTiO3 photodetector.